InDesign type : professional typography with Adobe InDesign - French, Nigel (Adobe Press, 2018)
Typography is the foundation of all graphic design. And if there's one sure way to improve as a graphic designer, it's to become more confident and more sophisticated in your use of type. This fully updated fourth edition is a comprehensive guide to creating professional type with Adobe InDesign. It covers micro and macro typography concepts, from understanding the nuance of a single spacing width to efficiently creating long and complex documents. InDesign Type shows not just how to use InDesign's extensive type features, but why certain approaches are preferable to others, and how to avoid common mistakes. Whether you're creating a single-page flyer or a thousand-page catalog, whether your documents will be printed or viewed on screen, InDesign Type is an invaluable resource for getting the most out of InDesign's typographic toolset. InDesign Type provides: " An exclusive focus on the typographic capabilities of InDesign " Complete coverage of macro and micro typography in InDesign " Clear, engaging explanations of the why and the how of good typography